Effects of Nano B4C Addition on the Solidification Behavior of Al-2219 Alloy Composites - Amit Bhumarker Singh; Abhishek Singh (International Journal of Manufacturing and Production Engineering, 2024)
The inclusion of nano B4C particulates in Al-2219-Nano B4C alloy was investigated to understand their impact on hardness and wear characteristics. 500 nm-sized nano B4C particulates are used as reinforcements for structures in the Al2219 alloy matrix. The nanocomposites were fabricated using the two-stage liquid stir melt method with varying weight percentages (2, 4, 6, and 8 wt. %) of Nano B4C in the Al-2219 alloy matrix. Renewable energy dispersive spectroscopy (EDS) and a scanning electron microscope (SEM) were used for analyzing the specimens' microstructure. Hardness and wear strength were assessed in accordance with ASTM standards. The even distribution of nano B4C particles in the Al-2219 alloy was confirmed by SEM images and confirmed by EDS analysis. Moreover, the base Al-2219 alloy's the toughness and wear vitality were enhanced by the addition of nano B4C particles.
Keywords: Al-2219 alloy matrix; Hardness; Scanning electron Microscope; energy dispersive spectroscope; liquid stir melt method; nano B4C particles; wear strength